Cementless primary or revision stem in revision hip arthroplasty for aseptic stem loosening with Paprosky type I/II femoral defect?. Issue 11 (10th August 2022) - Pai, Fu-Yuan; Arthur Chou, Te-Feng; Ma, Hsuan-Hsiao; Chang, Wei-Lin; Tsai, Shang-Wen; Chen, Cheng-Fong; Wu, Po-Kuei; Chen, Wei-Ming
Abstract : Background: The use of primary or revision stem during revision total hip arthroplasty (THA) for aseptic stem loosening with Paprosky type I/II femoral defect remains controversial. The aim of this study was to compare the outcomes of patients who underwent revision THA with a primary or revision stem. Methods: We retrospectively reviewed 78 patients who received revision THA for aseptic stem loosening using primary (N = 28) or revision stems (N = 50). The bone defects were classified as Paprosky type I or II. The mean follow-up duration was 72.3 ± 34.7 months. The primary outcome domains included surgical complications and implant failures. The secondary outcome domains included medical complications, 30- and 90-day readmission, and Harris hip score (HHS). Results: The use of revision stem was associated with a higher incidence than primary stem of patient complications (60.0% vs. 32.1%, p = 0.018), including intraoperative femur fracture (28.0% vs. 7.1%, p = 0.029) and greater trochanter fracture (16.0% vs. 0%, p = 0.045). The implant survival rate was comparable between groups. HHS at the final follow-up was similar. Conclusion: With a lower risk of surgical complications and a similar rate of mid-term implant survival, cementless primary stem appears superior to revision stem in revision THA for aseptic stem loosening with Paprosky type I/II femoral defect.